Epidemiological trends and outcomes of extensively drug-resistant tuberculosis in Shandong, China - Xiao-chun He; Ning-ning Tao; Yao Liu; Xian-xin Zhang; Huai-chen Li (BMC Infectious Diseases, 2017)
Abstract Background Extensively Drug-Resistant (XDR) Tuberculosis (TB) has posed a great threat to global health and finance systems, especially for developing countries with high TB and Multidrug-Resistant (MDR) TB burden. Methods We retrospectively analyzed HIV-uninfected TB case confirmed and treated in Shandong Provincial Chest Hospital (SPCH) between January 2008 and December 2015. Unique characteristics of XDR-TB were identified; its longitudinal changes and survival were analyzed. Results Between January 2008 and December 2015, a total of 144 cases were confirmed to be XDR-TB (2.5% of 5663 culture-confirmed TB cases; 27.9% of 516 MDR-TB cases). The proportion of XDR TB cases among MDR-TB cases has increased from 26.5% in 2008 to 44.5% in 2014 (Chi-Square test for trends: P < 0.01). Among the 144 XDR-TB cases, 21 patients (14.6%) had treatment success, 123 (85.1%) had poor treatment outcomes. Mortality was higher among XDR-TB cases than among MDR TB cases (8.3% vs. 3.8%, P = 0.033) and drug-susceptible TB cases (8.3% vs. 2.1%, P < 0.01). Conclusions XDR-TB cases comprise a substantial and increasing fraction of MDR-TB cases, causing poor treatment outcomes and high mortalities. Early drug susceptibility testing, adequate TB treatment and efficient infection control must be in place in future TB control strategies.